Industrialization and Economic Growth in Sub-Saharan Africa: The Role of Human Capital in Structural Transformation - WONYRA, Kwami Ossadzifo (Journal of Empirical Studies, 2019)
The objective of this paper is to analyze the impact of the manufacturing sector on economic growth through the role of human capital. Our data cover Sub-Saharan African (SSA) countries from 1990 to 2015. We use fixed effects, random-effects and Hausman-Taylor estimators. We take into account the unobservable characteristics of countries by including fixed effects or random effects in the model. Our results show that the manufacturing sector through its value added has a positive impact on economic growth in SSA countries. In addition, the interacting models show that the quality of human capital is an accelerator of the role of the manufacturing sector. The coefficient of the catch-up term is negative and significant in all models indicating that countries with a larger productivity gap relative to China are developing faster than countries closer to China. This finding is consistent with the convergence effects usually found in growth model estimates, which are either related to convergences towards a stable state or to a catching-up of growth linked to the international diffusion of knowledge.